Type II supernovae from the Carnegie Supernova Project-I: II. Physical parameter distributions from hydrodynamical modelling - Martínez, Laureano (2022)
Fil: Martinez, Laureano. Instituto de Astrofísica de La Plata, CONICET-UNLP; Argentina